FEATURES OF THE FUNCTIONAL STATE OF MUSCLE TISSUE IN ELDERLY PATIENTS WITH URGENT SURGICAL PATHOLOGY (World Science, 2021)
Sarcopenia is an important factor in the occurrence of complications in elderly patients with urgent surgical pathology. Decreased muscle strength and function is an important criterion for impaired early activation of such patients, which increases the number of complications and length of stay in the clinic. Identification of functional disorders of muscle tissue, as well as other metabolic disorders, such as type 2 diabetes, disorders of lipid metabolism, is important for the appointment of an adequate complex of intensive care. Prescribing levocarnitine and D-fructose-1,6-diphosphate sodium salt of hydrate is an important part of the treatment program in such patients.